2018
DOI: 10.1177/2156759x18824269
|View full text |Cite
|
Sign up to set email alerts
|

Data-Driven School Counseling: The Role of the Research–Practice Partnership

Abstract: Research-practice partnerships (RPPs) are ripe contexts for school counselors to employ data-driven practices to improve student outcomes. We leveraged an RPP between two universities and a high school to assist the latter's school counseling department in examining students' satisfaction with their counselor interactions. The RPP created the capacity for the counselors to gather and use data to implement targeted interventions for improving students' awareness and perceptions of their school counselors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Of the three components inherent in evidence-based school counseling, the school counseling profession has historically focused the most on data-driven and accountability practices (Gysbers, 2004). Practitioners have been provided strategies for implementing data-driven decision-making approaches to facilitating a comprehensive school counseling program (Hartline & Cobia, 2012;Poynton & Carey, 2006;Savitz-Romer et al, 2019) and strategies for implementing accountability approaches that demonstrate student outcomes resulting from school counseling interventions (Astramovich, 2016;Astramovich, Hoskins, & Coker, 2013;Maras, Coleman, Gysbers, Herman, & Stanley, 2013;Sink, 2009;Stone & Dahir, 2011). School counselors have reported various levels of program evaluation and accountability skills (Astramovich, 2016;Maras et al, 2013;Young & Kaffenberger, 2015), with professional development (Young & Kaffenberger, 2015) and mentorship (Maras et al, 2013) found to make a positive impact on the use of data and accountability strategies by school counselors (Astramovich, 2016).…”
Section: Evidence-based School Counseling: a Brief Reviewmentioning
confidence: 99%
“…Of the three components inherent in evidence-based school counseling, the school counseling profession has historically focused the most on data-driven and accountability practices (Gysbers, 2004). Practitioners have been provided strategies for implementing data-driven decision-making approaches to facilitating a comprehensive school counseling program (Hartline & Cobia, 2012;Poynton & Carey, 2006;Savitz-Romer et al, 2019) and strategies for implementing accountability approaches that demonstrate student outcomes resulting from school counseling interventions (Astramovich, 2016;Astramovich, Hoskins, & Coker, 2013;Maras, Coleman, Gysbers, Herman, & Stanley, 2013;Sink, 2009;Stone & Dahir, 2011). School counselors have reported various levels of program evaluation and accountability skills (Astramovich, 2016;Maras et al, 2013;Young & Kaffenberger, 2015), with professional development (Young & Kaffenberger, 2015) and mentorship (Maras et al, 2013) found to make a positive impact on the use of data and accountability strategies by school counselors (Astramovich, 2016).…”
Section: Evidence-based School Counseling: a Brief Reviewmentioning
confidence: 99%
“…At the time this current article was going to print, others had also recently published on the partnership between universities and school counselors. These include (a) Martin and colleagues (2019), who focused on evidence-based practices; (b) Savitz-Romer and colleagues (2018), who discussed data-driven school counseling; and (c) Stone and Eggleston (2020), who highlighted a social justice–driven partnership to decrease student attainment gaps. Hence, at the time of the present study, to our knowledge, our investigation was one of the first to empirically describe the district–university partnerships noted by Kaffenberger and colleagues (2006), offering a rich account into district supervisors’ related experiences.…”
Section: Discussionmentioning
confidence: 99%
“…In this special issue, Novakovic et al build upon previously identified models for training future school counselors in EBP (Zyromski, Dimmitt et al, 2018) and provide a method for integrating EBSC and social justice advocacy that infuses social justice training within the EBP preparation throughout students' internship. These school counselor educators took advantage of the opportunity to train future school counselors in EBP by expanding the focus from providing them with the knowledge and skills to use data (Michel, Lorelle & Atkins, 2018;Savitz-Romer et al, 2019;Young et al, 2014) to using an EBP approach to advocate for social justice. The use of EBSC to increase equity and access for underrepresented populations is a critical focus for our field.…”
Section: Challenges and Opportunities For Ebscmentioning
confidence: 99%
“…Excitingly, our profession is actively grappling with the implications of engaging in evidence-based practices (EBP). In the past year, multiple authors (Borders, 2019;Mullen et al, 2019;Parrow et al, 2019) have explored several topics directly related to EBP in school counseling, while other authors (Savitz-Romer et al, 2019;Warren & Mauk, 2020) have written about issues ancillary to EBP such as research practice partnerships in schools and implementation science in school counseling, respectively. This special issue of Professional School Counseling provides insight into the conference proceedings of the Evidence-Based School Counseling Conference (EBSCC; http:// www.ebscc.org) and to creating an opportunity to continue discussions about ways we can ongoingly evolve our conceptualization of evidence-based school counseling EBSC.…”
mentioning
confidence: 99%